Determinantes da arrecadação de ICMS de importação no estado do Ceará - Lima, Claudia Sousa (2017)
The ICMS is one of the main sources of revenue for the Brazilian states, in addition it is used by the federal entities to attract investments. This tax is also levied on imported goods and services, so ICMS-Import can be used to implement trade policy measures. Given the importance of foreign trade policy for development, this paper proposes to analyze which factors have an impact on the collection of ICMS for imports and which are influenced by it. To reach the results, time-series methods were used. The variables candidates to explain the behavior of ICMS-import were the main groups of products imported by the State of Ceará in recent years and the exchange rate. These variables were not cointegrated, therefore we chose to estimate a VAR in differences. Imports of the metals group and the exchange rate were the most representative in the explanation of the import tax. These variables also had the most significant impacts on the impulse response function.